Correction: A new 3D finite element-based approach for computing cell surface tractions assuming nonlinear conditions. - Silvia Hervas-Raluy; Maria Jose Gomez-Benito; Carlos Borau; Mar Cóndor; Jose Manuel Garcia-Aznar (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0249018.].